Peran Guru dalam Mengintegrasikan Pendidikan Karakter di Sekolah Dasar - Nurjana (Yayasan Darussalam Bengkulu, 2024)
Character education is one of the important aspects in early childhood development, especially at the Elementary School (SD) level. This study aims to examine the role of teachers in integrating character education into the learning process in elementary schools. Using qualitative research methods, this study involved observation, in-depth interviews, and document analysis to collect data from six elementary school teachers who were experienced in teaching character education. The results showed that teachers act as role models, facilitators, and motivators in integrating character values ​​into the curriculum. Teachers use various strategies, such as project-based learning, group discussions, and positive behavioral reinforcement to instill values ​​such as honesty, responsibility, and cooperation in students. This study found that challenges faced by teachers include lack of support from the school and limited resources. Thus, recommendations are given to improve teacher training and provide adequate resources to support the integration of character education in schools. This study is expected to provide insights for stakeholders in efforts to improve character education in elementary schools.